Financial reporting in hyperinflationary economies and the value relevance of accounting amounts: hard evidence from Zimbabwe - Chamisa, Eddie; Mangena, Musa; Pamburai, Hamutyinei Harvey; Tauringana, Venancio (Review of Accounting Studies, 2018)
We examine the value relevance of inflation-adjusted (IA) and historical cost (HC) amounts in a hyperinflationary economy. Using a unique dataset drawn from annual reports of firms listed on the Zimbabwe Stock Exchange from 2000 to 2005, we find that both sets of amounts are value relevant but HC amounts are superior to IA amounts. We also show that inflation gains and losses provide incremental information content beyond that provided by the HC amounts and that the power of this incremental content model is equivalent to that of the HC model but superior to that of the IA model. Further analyses indicate that, in periods of relatively low inflation, HC amounts are more value relevant, while in periods of relatively high inflation, the two sets of amounts are equally value relevant. Finally, we show that HC amounts have a greater ability to predict future cash flows than IA amounts, which suggests that the superiority of their value relevance stems from this.